The mission of preaching equipping the community for faithful witness - Johnson, Patrick W. T. 1979- (Downers Grove InterVarsity Press, 2015)
Cover; Title Page; Copyright; Dedication; Contents; Foreword; Acknowledgments; Abbreviations; Introduction; 1 The Preacher as Witness; The Witness of Preaching; Preaching as Testimony; Confessing Jesus Christ; Toward a Missional Ecclesiology; 2 The Witness of the Christian Community; Barth's Ecclesiology and Its Place in Missional Theology; "The Holy Spirit and the Sending of the Christian Community"; Moving Toward a Missional Homiletic; 3 The Witness of Missional Congregations; The First Pattern: Discerning Missional Vocation; The Second Pattern: Biblical Formation and Discipleship.
Preaching Confesses Jesus Christ Through a Missional Interpretation of Scripture . . . To Equip the Community for Witness to the WorldConclusion; Bibliography; Name and Subject Index; Praise for The Mission of Preaching; About the Author; More Titles from InterVarsity Press; IVP Academic Textbook Selector.
The Third Pattern: Taking Risks as a Contrast CommunityThe Fourth Pattern: Practices That Demonstrate God's Intent for the World; The Fifth Pattern: The Public Witness of Worship; The Sixth Pattern: Dependence on the Holy Spirit; The Seventh Pattern: Pointing Toward the Reign of God; The Eighth Pattern: Missional Authority; Moving Toward a Missional Homiletic; 4 A Missional Homiletic of Witness; Preaching; Preaching Confesses Jesus Christ; The Preacher Confesses Jesus Christ; Preaching Confesses Jesus Christ Through a Missional Interpretation of Scripture.
We hear plenty of discussion about missional theology, missional leadership and missional church planting. But what about missional preaching? Now that the church in the West lives within a post-Christendom context, how should preaching look different? What homiletical assumptions arose within Christendom but are no longer relevant for a missionary church? In The Mission of Preaching, Patrick W. T. Johnson develops the first missional homiletic, a model for preaching determined by the missionary encounter between the gospel and Western culture. Mobilizing the latest resources
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Witness bearing (Christianity); Preaching; Evangelistic work; RELIGION / Christian Ministry / Preaching